Peningkatan Keterampilam Motorik Kasar Melalui Kegiatan Tari Binatang pada Anak Kelompok B TK PGRI I Langkap - Denok Dwi Anggraini; St Aini Farah Dhiba; Asmi Ittari (PG-PAUD Trunojoyo, 2016)
The purpose of this research was to increasing gross motor skilsl of child through animal dance in group B TK PGRI 1 Langkap. This research was done because there are problems in gross motor skilsl in child in group B TK PGRI 1 Langkap. This research is colaborative classroom action research. by using the procedure of th model study  Kemmis Mc Taggart. Subject in this research were children in group B TK PGRI 1 Langkap totaling 15 children conisting ot 8 boys and 7 girls. The Object of  this research is the gross motor skils that indicator of strength, coordination and agility. The technique used to collect the data of observation and interview. Analysis of data using qualitative descriptive. The Animal dance activities carried out in stage with teaching dance moves step by step from one movement to the next movement resulting in increased gross motor skils in each cycle. The results showed that animal dance activiting can improve gross motor skills of child. Increasing can be seen in the results of the research the pre-condition gross motor skills of child by 11.11%, after the action o the first cylce gross motor skills of children’s increased to 33.3%, in thr second cycle gross motor skill of children increased to 84.44%.. The research was stopped in the second cycle because the already meets the criteria of success indicators.